Boma Trials on the Use of the Gregarious-Adult Pheromone Phenylacetonitrile of the Desert Locust Schistocerca gregaria (Forskål, 1775) and Metarhiziumacridum in the Management of Nymphs (University of Khartoum Journal of Agricultural Sciences, 2023)
The trials were conducted within plastic Bomas (10 x10meters each) in a farm at Sallom (19 38 55 N X 37 15 37 E) 45 kilometersSouth West of Port Sudan, Sudan. Approximately 1000 fourth instarnymphs of the Desert Locust Schistocerca gregaria (Forskål, 1775) wereused per replica in each test. Each test was replicated three times. Thetreatments included different dosages of Metarhizium acridum alone orincorporated with the Desert Locust gregarious adult pheromonePhenylacetonitrile (PAN). The results indicated that the cumulativemortality rate in day 15 at the end of the tests was 0.994±0.010 withMetarhizium 50 g/ ha. (recommended dose). The rates were 0.991±0.001and0.967±0.003 with fractional doses of Metarhizium, 25g/ha +PAN and12g/ha + PAN respectively. When PAN was used alone, the cumulativemortality at day 15 was 0.739 ± 0.017. The same trend in the mortalityrate was also evident when the control efficiency was examined. Theefficiency in day 15 was 99.32 ± 0.001 with Metarhizium 50 g/ ha.(recommended dose). The rates were 98.75 ±0.056, 96.33±0.30 and72.78±0.45 with fractional doses of Metarhizium 25g/ha +PAN, 12g/ha+PAN and 6g/ ha +PAN respectively. Control efficiency was 71.82±1.82and 3.70±1.86 with PAN alone and Diesel respectively. Examination of
Keywords: Contro; Desert Locust; Phenylacetonitrile (PAN)